Guitar System Makes Waves. (Downbeat, 2006)
The article features Waves' new GTR (Guitar Tool Rack) to let music engineers, producers an session guitarists get high-quality sound from a guitar plugged directly into a digital audio workstation. It is designed with a three-part integrated hardware/software solution that includes Waves/ PRS Guitar Interface, Waves Amp plug-in, Waves Stomp plug-in and Waves Tuner plug-in.